2012
DOI: 10.1177/1748048511426988
|View full text |Cite
|
Sign up to set email alerts
|

Invasion vs occupation

Abstract: This study aimed to determine how well embedded reporters perceived they covered the Iraq War and whether those attitudes have changed over time. While findings suggested embeds continue to judge their overall performance as positively in 2005/6 as in 2004, respondents largely recognized problems with the embedding process. Data analysis indicated after the official declaration of victory that embedded reporters became significantly less likely to agree that embeds were qualified for their job. Professional va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition, extant works have focused on journalists' perceptions of their environment and of their subsequent performance, instead of examining the actual changes in media content and coverage. Nonetheless, journalists working in deadly news-gathering environments have reported that increases in danger affects the topics they covered and how they covered them (Fahmy and Johnson 2012). Threatened reporters in Iraq explicitly decided not to write on controversial topics and refrained to travel for assignments that could put them at an even greater risk, even if that meant being unable to cover a key political event (Kim and Hama-Saeed 2008).…”
Section: Reporting In Risk-prone Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, extant works have focused on journalists' perceptions of their environment and of their subsequent performance, instead of examining the actual changes in media content and coverage. Nonetheless, journalists working in deadly news-gathering environments have reported that increases in danger affects the topics they covered and how they covered them (Fahmy and Johnson 2012). Threatened reporters in Iraq explicitly decided not to write on controversial topics and refrained to travel for assignments that could put them at an even greater risk, even if that meant being unable to cover a key political event (Kim and Hama-Saeed 2008).…”
Section: Reporting In Risk-prone Regionsmentioning
confidence: 99%
“…Beyond the news media routines and organizational policies that may affect media coverage amid violence, journalism scholars have also examined the role of extra-media influences, looking into the effects of violent environments and threats exerted by both state and non-state armed actors attempting to affect the flow of information. Related claims and findings are, however, limited and have mainly concentrated on individuals’ journalistic experiences while covering conflicts in Iraq (Kim 2010; Kim and Hama-Saeed 2008; Fahmy and Johnson 2012). In addition, extant works have focused on journalists’ perceptions of their environment and of their subsequent performance, instead of examining the actual changes in media content and coverage.…”
Section: Reporting In Risk-prone Regionsmentioning
confidence: 99%
“…As one of its authors (Reese, 2007) said it should be, this model has been widely used in diverse studies worldwide (e.g., Fahmy & Johnson, 2012;Kwanda & Lin, 2020;Milojević & Krstić, 2018;Xu & Jin, 2017). Regarding the Mexican case, Relly and González (2014) analyzed antipress violence in the Northern region, adding a new level to Shoemaker andReese's (1996, 2014) scheme with Intermedia Influences related to journalist networks.…”
Section: Analytical Framework: the Hierarchy Of Influences Modelmentioning
confidence: 99%
“…Several scholars have applied the hierarchy of influences model (Shoemaker and Reese, 1996; Reese and Shoemaker, 2016) as a framework to understand influences on journalists’ role as newsmakers in different national and cultural contexts (Fahmy and Johnson, 2012; Ittefaq et al, 2021; Kim, 2010; Reese, 2001; Relly and Gonzalez de Bustamante, 2014; Ullah and Jan 2021). The hierarchy of influences model provides a framework for understanding influences on journalists’ role as newsmakers based on five levels including the individual characteristics of journalists, their work routines, organizational influences, extra-media, and social systems.…”
Section: Introductionmentioning
confidence: 99%